Enhancing haemophilia care through registries. (May 2014) - Dolan, G.; Makris, M.; Bolton‐Maggs, P. H. B.; Rowell, J. A.
Summary: Clinical registries or databases have an increasing role in the management of inherited bleeding disorders. Initially, research‐based registries provided valuable data and now national databases are increasingly being developed with multiple stakeholders, including persons with haemophilia (PWH) and payers, to enable improvements and efficiencies in care. Registries are extending to international collaborations to collect adverse event data and comparisons of national approaches to the management of haemophilia to improve the availability of product to PWH.